PENGARUH E-PROMOTION, E-COMMERCE, E-SERVQUAL DAN BRAND AMBASSADOR TERHADAP MINAT BELI ULANG DI SHOPEE PADA GENERASI Z DI KOTA DENPASAR - Ni Made Ratih Safitri; I Gusti Ayu Imbayani; I Made Surya Prayoga (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Generation Z or digital native generation is a generation that grew up in an all-digital environment. Generation Z is the preferred segment by marketers because of their large population in today's world and generation Z tends to consume and use almost all of their income to consume or buy a product with online shopping methods that provide an experience so that marketers need to increase marketing activities on the company's online media so that Generation Z can get interesting information and influence the behavior and buying interest of consumers. This study aims to analyze the effect of e-promotion, e-commerce, e-servqual and brand ambassadors on the intention to repurchase at shopee in Generation Z in Denpasar. This research was conducted in the city of Denpasar with generation Z respondents who use Shopee. The types of data used in this study are qualitative and quantitative data. While the source uses primary and secondary data. With the number of samples taken as many as 167 respondents with non- probability sampling methods. This data was collected by means of literature study, questionnaires and documentation. This data was analyzed using multiple linear regression analysis assisted by the SPSS version 24 program. The results of this study indicate that the e-servqual and brand ambassador have a significant positive effect on repurchase intention. While the variable e-promotion, e- commerce does not have a positive effect on repurchase interest.